The Gap in Access to Marriage Guidance: A Policy Study to Reduce Child Marriage in East Java - Andik Suyitno (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper describes that high number of marriage dispensation requests in East Java indicates a systematic failure in protecting children from early marriage. This study aims to comprehensively analyze the causal factors, including: 1) the limited authority of the Office of Religious Affairs (KUA) in stopping child marriage; 2) disparities in access to marriage guidance (Binwin) due to geographical, socio-economic, and educational constraints; and 3) operational limitations of Binwin services, such as a lack of innovation, schedule flexibility, and adequate human resources. This policy paper uses a qualitative methodology with a descriptive analysis approach and literature review. Primary data were collected from various official documents of the Ministry of Religious Affairs, policy paper reports from research institutions, and scientific journal publications relevant to the issues of child marriage, marriage guidance, and public policy. Data analysis was conducted using descriptive-analytical techniques, where the collected data were organized, interpreted, and synthesized to identify patterns, causal relationships, and existing gaps. The results are expected to serve as a basis for formulating alternative policies that focus on strengthening the role of the KUA, improving access and quality of Binwin services through digital innovation, and more inclusive communication strategies. Thus, this study contributes to holistic efforts to reduce child marriage rates and build more resilient families.